New sweet cherries enrich fruit basket - Srivastava, K K; Kumar, Dinesh; Singh, S R; Pandey, G; Singh, D B (Indian Horticulture, 2019)
In order to document the development of new varieties, CITH, Kashmir, initiated the rigorous survey from year 1996 under the institute research project "Survey, collection, characterization and documentation of temperate horticultural crops". The institute identified and collected variability from the centuries old varieties namely Biggareau Napoleon, Bigarreau Noir Grossa, Guigne Noir Hative etc. Presently, institute germplasm bank have 30 sweet and sour cherry genotypes. Of these, four promising type namely, CITH-Cherry-03, CITH-Cherry-05, CITH-Cherry-07 and CITH-Cherry-09 were identified.